BDNF mRNA Expression in Leukocytes and Frontal Cortex Function in Drug Use Disorder - Anders, Quézia Silva; Ferreira, Leonardo Villaverde Buback; Rodrigues, Livia Carla de Melo; Nakamura-Palacios, Ester Miyuki (Frontiers in Psychiatry, 2020)
The brain-derived neurotrophic factor (BDNF) is a neurotrophin recognized to play a major role in neuroplastic modifications associated to drug abuse, being involved in various behavioral changes found in drug use disorders, such as drug sensitization, craving and relapses. These neuroplastic changes were shown to affect the prefrontal cortex functions, which can be briefly measured through cognitive tests such as the Frontal Assessment Battery (FAB). In this study we investigated the BDNF mRNA expression in peripheral blood lymphocytes of crack-cocaine use disorder (CUD) and alcohol use disorder (AUD) patients, after drug detoxification treatment, using a real-time PCR approach and examining its association to FAB performance. BDNF mRNA expression was found to be higher by 2.25-fold in CUD patients and by 2-fold in the AUD patients when normalized to controls, and these values were found to be associated with FAB scores. This preliminary study evaluates, for the first time, BDNF mRNA expression in leukocytes and its relationship to FAB scores in crack-cocaine and alcohol use disorder patients.